Tinjauan Yuridis terhadap Pengesahan Perjanjian Internasional melalui Peraturan Presiden No.77 Tahun 2019 : Masalah Formil dan Substansi - Valentino Pattikawa (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study examines the ratification of the Multilateral Convention to Implement Tax Treaty Related to Measures to Prevent BEPS through Presidential Regulation (Perpres) No. 77/2019. This ratification raises legal issues because Law No. 24 of 2000 concerning International Agreements stipulates that the ratification of certain international agreements should be carried out through a Law or Presidential Decree. This study uses a normative legal method with a statutory approach to analyze the conformity of Perpres 77/2019 with Law No. 24 of 2000 and the theory of the hierarchy of legal norms. The results of the study indicate that Perpres 77/2019 is formally flawed because it conflicts with Law No. 24 of 2000, but in substance it is appropriate for use.